THE EFFECT OF NET INCOME, TOTAL CASH FLOWS AND SALES GROWTH ON STOCK PRICES (CASE STUDY ON FOOD AND BEVERAGES SUBSECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR 2016-2019) - Indrawati, Ressi; Suartini, Sri (Jurnal Ekonomi Balance, 2020)
This study aims to determine whether there is an effect of Net Income, Total Cash Flow, and Sales Growth on Stock Prices partially or simultaneously. The method in this research is a descriptive verification technique with a quantitative approach that comes from the annual budget report of the food and beverages sub-sector companies and literature studies. The sampling technique used the purposive sampling technique. The information used is secondary data which is analyzed through descriptive and verification analysis, data validity testing, multiple linear regression testing, and hypothesis testing using the coefficient of determination test, t-test, and f test. This investigation used the IBM SPSS version 25 software program to process data. The results of this study indicate that partially Net Income has a significant positive effect on Stock Prices, Total Cash Flow has no significant effect in a positive direction on Stock Prices, and Sales Growth has no significant effect in a positive direction on Stock Prices. Then simultaneously Net Profit, Total Cash Flow, and Sales Growth have a significant effect on Stock Prices together.